2014
DOI: 10.1159/000363420
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Features of Solid Pseudopapillary Neoplasms of the Pancreas at a Single Institution

Abstract: Aims: The aim of this study was to determine the clinicopathological features and surgical management of solid pseudopapillary neoplasms (SPNs) of the pancreas at a single institution. Methods: We investigated 34 patients (5 males and 29 females) who underwent surgery for pathologically confirmed SPNs between 1994 and 2012. Results: Clinical symptoms were absent in 58.8% of the patients. The median tumor diameter was 42.7 mm. All tumors were successfully removed by R0 resection. Pathologically, 5.9% had duoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
4
9
0
Order By: Relevance
“…32 The typical immunohistochemistry of SPNs includes positive staining for Vim, AAT, α-1-antichymotrypsin (AACT), and NSE, 33,34 but the unique immunohistochemical features with expression of PR and CD10 were not consistent. 8,35 According to recently published data, a particular dot-like intracytoplasmic expression of CD99 appears to be highly unique for SPN, 36,37 and this distinctive staining pattern was present in 86.9 % of our cases. Thus, CD99 accompanied by other useful markers would help establish the diagnosis of SPNs.…”
Section: Discussionsupporting
confidence: 56%
“…32 The typical immunohistochemistry of SPNs includes positive staining for Vim, AAT, α-1-antichymotrypsin (AACT), and NSE, 33,34 but the unique immunohistochemical features with expression of PR and CD10 were not consistent. 8,35 According to recently published data, a particular dot-like intracytoplasmic expression of CD99 appears to be highly unique for SPN, 36,37 and this distinctive staining pattern was present in 86.9 % of our cases. Thus, CD99 accompanied by other useful markers would help establish the diagnosis of SPNs.…”
Section: Discussionsupporting
confidence: 56%
“…No extensive lymphatic dissection was required because we only found one patient with lymph node metastasis in our study (the patient was suspected to pancreatic cancer so the lymph nodes (NO. 10,11,18) around the body and tail of the pancreas were dissected)this concurs with the previous findings of Suzuki et al 22 The role of neo-adjuvant or adjuvant chemotherapy, and radiotherapy, in the treatment of SPT is limited, 23,24 but Brunetti et al find an interesting result that a patient diagnosed to SPTP with malignant transformation treated with adjuvant chemotherapy achieved a longduration. 25 In the present study, we found that pancreatic fistulas were the predominant complication (n=21 patients); grade A fistulas were found in 19 patients, while grade B fistulas were found in two patients; we did not identify any grade C fistulas.…”
Section: Discussionsupporting
confidence: 88%
“…Most patients mention unspecific symptoms, while the rest are asymptomatic and accidentally diagnosed (15,16). Abdominal pain or painless palpable abdominal mass is the commonest presentation, as occurred in our series.…”
Section: Discussion Discussionsupporting
confidence: 49%